Early motor and mental development in very preterm infants with chronic lung disease. Issue 1 (1st July 2000) - Katz-Salamon, M; Gerner, E M; Jonsson, B; Lagercrantz, H
Abstract : BACKGROUND: The increased incidence of neurological deviations in preterm infants with chronic lung disease (CLD) has been linked to severe brain haemorrhage (intraventricular haemorrhage (IVH)) and periventricular leucomalacia (PVL) rather than to CLD per se. AIM: To evaluate whether CLD without concomitant brain lesions constitutes a risk factor for adverse developmental outcome. METHOD: Forty three very low birthweight infants with CLD, but without IVH or PVL, and 43 very low birthweight infants without CLD, IVH, or PVL were evaluated at 5 and 10 months of corrected age using the movement assessment of infants (MAI) scale. The Griffiths' developmental test was carried out at 10 months of age. RESULTS: The overall motor assessments (MAI) in infants with CLD and controls were not significantly different. However, differences were observed in the execution of volitional movements (MAI), the total sum, hand and eye coordination, and perception and intelligence (measured by the performance scale of the Griffiths' test). CONCLUSIONS: CLD has a deleterious effect on the control of hand and eye coordination and on perception and intelligence. These results thus re-emphasise the necessity for careful neurodevelopmental follow up of infants with CLD whether or not they suffered IVH or PVL.